2010
DOI: 10.1101/gad.553410
|View full text |Cite
|
Sign up to set email alerts
|

KSHV-encoded miRNAs target MAF to induce endothelial cell reprogramming

Abstract: Kaposi sarcoma herpesvirus (KSHV) induces transcriptional reprogramming of endothelial cells. In particular, KSHV-infected lymphatic endothelial cells (LECs) show an up-regulation of genes associated with blood vessel endothelial cells (BECs). Consequently, KSHV-infected tumor cells in Kaposi sarcoma are poorly differentiated endothelial cells, expressing markers of both LECs and BECs. MicroRNAs (miRNAs) are short noncoding RNA molecules that act post-transcriptionally to negatively regulate gene expression. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
132
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(138 citation statements)
references
References 54 publications
6
132
0
Order By: Relevance
“…Thus far, miRNA studies have been constrained by sensitivity limits for detection of individual miRNAs and for the discovery of miRNA-target interactions. Targets with functions that seem to befit the biology of B cell development, endothelial cell differentiation, and KSHV (such as BACH1, xCT, MAF, and others) have been individually validated (132)(133)(134). These are by no means the only targets, and it is anticipated that additional targets will be identified in the future.…”
Section: Viral Mirnas Support Viral Infection and Latent Persistencementioning
confidence: 99%
“…Thus far, miRNA studies have been constrained by sensitivity limits for detection of individual miRNAs and for the discovery of miRNA-target interactions. Targets with functions that seem to befit the biology of B cell development, endothelial cell differentiation, and KSHV (such as BACH1, xCT, MAF, and others) have been individually validated (132)(133)(134). These are by no means the only targets, and it is anticipated that additional targets will be identified in the future.…”
Section: Viral Mirnas Support Viral Infection and Latent Persistencementioning
confidence: 99%
“…It has been reported that KSHVinfected LECs show an up-regulation of genes associated with BECs. 4,23 We examined the LEC-to-BEC transcriptome reprogramming present in our array data to confirm that the KSHV infection For personal use only. on April 27, 2019. by guest www.bloodjournal.org From had been successful.…”
Section: Kshv Introduces Tumor Traits and Migration Potential Into Lymentioning
confidence: 99%
“…It has been reported that KSHVinfected LECs show an up-regulation of genes associated with BECs. 4,23 We examined the LEC-to-BEC transcriptome reprogramming present in our array data to confirm that the KSHV infection had been successful. By calculating the transcriptome distances between sample groups, we confirmed that KSHV-infected LECs were closer to BECs than parental LECs (supplemental Figure 1C).…”
Section: Kshv Introduces Tumor Traits and Migration Potential Into Lymentioning
confidence: 99%
“…Thus far, viral miRNAs have been identified in a number of DNA viruses, including members of the herpesvirus, polyomavirus, and adenovirus families (3)(4)(5). These viral miRNAs have been described to regulate their replication cycles (6, 7) and the cellular transcriptome (5,(8)(9)(10), and even to mimic endogenous miRNAs (11,12).…”
mentioning
confidence: 99%